The association between parenting, attachment formation and gender role orientation and its impact on accessing support when in need - Milovchevich, Darryl George (Curtin University, 2009)
Attachment theory suggests that children develop internalized expectations of primary care givers that predict the availability of care and protection offered by parents (Bowlby, 1969; 1973; 1980). Parenting practice has been found to significantly impact on the development of internalised attachment schemas (Nickell, et al., 2002). Both one’s attachment and conception of gender-role orientation, which define appropriate gender-based behaviour, have been found to correlate (Shaver, et al., 1996). Furthermore access to emotional support has been found to correlate with attachment (Fairchild & Finney, 2006) and genderrole orientation (Houle, et al., 2008). This study used data from a random community sample to explore the impact of recalled parenting experiences on attachment in romantic relationships, gender-role values and the development of emotional support networks. The randomised sample was also used to develop community norms for the Experiences in Close Relationships Questionnaire Revised (ECR-R; Fraley, Waller & Brennan, 2000). Results indicated the importance of paternal indifference and maternal over control in female attachment to romantic partners. Mental health symptoms differed depending on parenting practice experienced and the gender of the participant. Both romantic attachment and gender role orientation impacted on the nature and propensity to access emotional support. Finally, results supported the psychometric properties of the ECR-R.